A Survey on Retinal Area Detector Using SLO Images - Gopi, Greeshma; Kavitha, MR; Faisal, KK (International Journal of Computer Sciences and Engineering, 2025)
Scanning Laser ophthalmoscopes (SLOs) are going to be used for early detection of retinal diseases. it's a method of examination of the attention. The advantage of exploitation SLO is its wide field of scan, which can image associate outsized an area of the membrane for higher identification of the retinal diseases. On the opposite aspect, throughout the imaging methodology, artefacts like eyelashes and eyelids are also imaged in conjunction with the retinal space. This brings an enormous challenge on the thanks to exclude these artefacts. In planned novel approach to automatically extract out true retinal house from associate SLO image based mostly on image method and machine learning approaches. the straightforward Linear unvaried cluster (SLIC) is that the rule utilised in super-pixel calculation. To decrease the unpredictability of image preparing errands and supply associate advantageous primitive image vogue. to scale back the quality of image method tasks and provide a convenient primitive image pattern, conjointly to classified pixels into utterly totally different regions primarily based on the regional size and compactness, referred to as super-pixels. The framework then calculates image based mostly choices reflective textural information and classifies between retinal house and artefacts. The survey presents different methods that are used to detect the artefacts.